Implikasi Putusan MK No. 90/PUU-XXI/2023 terhadap Fungsi Rekrutmen Politik Demokratis di Indonesia: The Implications of Constitutional Court Decision No. 90/PUU-XXI/2023 on the Function of Democratic Political Recruitment in Indonesia - Alvito Adiansyah; Aulia Putri Maharani; Fairuz Arkan Fatihah; Lia Wulandari (LITERA: Jurnal Ilmiah Mutidisiplin, 2026)
This study analyzes the implications of Constitutional Court Decision No. 90/PUU-XXI/2023 on the function of elections in democratic political recruitment in Indonesia. The decision revised the age requirement for presidential and vice-presidential candidates, permitting individuals under 40 to run if they previously held an elected office, sparking controversy over alleged conflicts of interest and ethical violations. This research employs a qualitative case study approach, with data obtained through documentary study of the Constitutional Court's decision, the Constitutional Court Honorary Council's ruling, and relevant academic literature, analyzed using content analysis through Schumpeter's concept of electoral democracy and Dahl's theory of polyarchy. The findings reveal three conclusions: first, the change in candidacy requirements amid an ongoing electoral cycle violated the principles of equality and competitive stability; second, the proven ethical violation by the Chief Justice showed that the recruitment process lacked institutional independence; and third, the decision risks becoming a medium-term legal precedent that strengthens oligarchy and political dynasties, threatening future political recruitment. Overall, these findings indicate that the function of elections as a democratic recruitment mechanism has been distorted at the substantive and institutional levels, underscoring the need for judicial independence, regulatory stability, and fair political competition to sustain Indonesian democracy.